Risk assessment of trihalomethanes exposure by consumption of IV gamma products: Evidences from a Portuguese regional survey - Simões, Cátia (2021)
Due to the current demand for healthier food, the IV gamma products industry has grown over the years. Additionally, it is well known that chlorine is a disinfectant largely used in this industry. However, the risk assessment associated with the formation of carcinogenic by-products from this halogenated disinfection has not been widely studied. The aim of this study was to assess the trihalomethanes (THMs) exposure through the consumption of IV gamma products, more specifically, salad mixes, and potential health risk in Portuguese population using a deterministic method. The quantification of THMs in salad mixes from the most representative Portuguese brands was performed by gas chromatography coupled to mass spectrometry (GC–MS). The THMs exposures were estimated by combining the THMs concentration data with a ready-to-eat salad mix consumption survey (case study applied in the Lisboa e Vale do Tejo area; n = 271). The concentration of THMs in all samples was below the limit of quantification of the equipment (1 μg/L), and this limit was used for the evaluation of the exposure. It was found that it is very small for the consumption pattern of these products in the studied population categories, suggesting that there is no risk for consumers due to the halogenated disinfection process. The highest estimated daily exposure was 7,65X10−5 mg/ kg bw/ week, which corresponds to a person who consumes such products daily.